Badische Anilin & Soda-Fabrik dye label with anchor (Badische Anilin- & Soda-Fabrik, 1900)
Dye label depicts an anchor in front of a body water with cresting waves. Illustration is surrounded by an elaborate border with the Badische Anilin & Soda-Fabrik (BASF) trademark insignia. Founded in 1865, Badische Anilin & Soda-Fabrik (BASF) was once the largest chemical factory in the world. Based in Ludwigshafen, Germany, the company first concentrated on the manufacture of synthetic dyestuffs. Key breakthroughs came in the form of the industrial production of synthetic indigo (1897) and the discovery of the indanthrene dyes (1901). Aniline dyes determined much of the firm's business. The company primarily advertised by submitting its products for awards at regional and international industrial trade fairs, especially world's fairs.
Keywords: Badische Anilin- & Soda-Fabrik; Advertising; Dye industry; Dyes and dyeing; Printed ephemera